A Corporate Solution to Global Poverty : How Multinationals Can Help the Poor and Invigorate Their Own Legitimacy - Lodge, George C. (Princeton University Press, 2006)
World leaders have given the reduction of global poverty top priority. And yet it persists. Indeed, in many countries whose governments lack either the desire or the ability to act, poverty has worsened. This book, a joint venture of a Harvard professor and economist with the international Finance Corporation, argues that the solution lies in the creation of a new institution, the World Development Corporation (WDC), a partnership of multinational corporations (MNCs), international development agencies, and nongovernmental organization (NGOs). In A Corporate Solution to Global Poverty, George Lodge and Craig Wilson assert the MNCs have the critical combination of capabilities required to build investment, grow economies, and create jobs in poor countries, and thus to reduce poverty. Furthermore, the contend, MNCs can do so profitably and this sustainably. But they lack legitimacy, and risk can be high, and so a collective approach is better than one in which an individual company proceeds alone. This a UN-sponsored WDC, owned and managed by a dozen or MNCs with NGO support, will make a marked difference. At a time when big business has been demonized for destroying the environment, enjoyed one-sided benefits from globalization, and deceiving investors, the book argues the MNCs have much to gain from becoming more effective in reducing global poverty. This is not a call for philanthropy. Lodge and Wilson believe that corporate support for the World Development Corporation will benefit not only the world's poor but also company shareholders as a result of improved MNC legitimacy and stronger markets and profitability.